2009
DOI: 10.21091/mppa.2009.3024
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Frequency of Postural Flaws During Violin Performance

Abstract: There is much evidence to show postural flaws occurring in violin players during performance. The general objective of this study was to observe violinists during performance for the appearance of postural flaws and the frequency with which these flaws occurred. For this work, 20-minute video recordings were made of four student violinists from an orchestra; the violinists were recorded from a frontal viewpoint, and also anatomic markers were placed on them in order to separately analyze some of the arm and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In addition to gross motor movements of the arm, the fine motor movements made by the hand are essential to proper bowing technique (Kruta de Araújo et al, 2009). Wiesendanger et al (2006) found that holding the bow requires a precise force control between the right-hand fingers, especially the thumb and the middle finger.…”
Section: Grip Patterns In Bow-hold Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to gross motor movements of the arm, the fine motor movements made by the hand are essential to proper bowing technique (Kruta de Araújo et al, 2009). Wiesendanger et al (2006) found that holding the bow requires a precise force control between the right-hand fingers, especially the thumb and the middle finger.…”
Section: Grip Patterns In Bow-hold Developmentmentioning
confidence: 99%
“…This leads violin pedagogues to pay great attention to the different functions of the joints of the shoulder, arm, and the individual fingers and their role in making subtle adjustments needed to achieve the desired tone (Pyykönen, 2015). Kruta de Araújo et al (2009) identified the following basic right-arm movements used in violin playing:…”
Section: Proximodistal Development and Bowing Techniquementioning
confidence: 99%
See 3 more Smart Citations